Acoustic energy harvesting enhanced by locally resonant metamaterials - Ma, Ke-Jing; Tan, Ting; Liu, Feng-Rui; Zhao, Lin-Chuan; Liao, Wei-Hsin; Zhang, Wen-Ming (Smart materials and structures, 2020)
Acoustic energy harvesting has the potential to power small-scale electronic applications and attracts wide attention. This paper presents a two-dimensional local resonant metamaterial energy harvester. The defect in the metamaterial which can induce local resonance is utilized to enhance energy harvesting. The defect mode and key parameters of the local resonant metamaterial energy harvester which can generate the maximum voltage are determined by theoretical analysis and simulations. The experiments were conducted in a hemi-anechoic room. The output voltage and transmission spectra of the local resonant metamaterial energy harvester are basically consistent with the simulations. The experimental results show that the voltage of the local resonant metamaterial energy harvester can be enhanced 950% compared with that of the bare plate energy harvester. The maximum power density of the local resonant metamaterial energy harvester is 1.24 mW cm−3. Moreover, the maximum voltage generated by the local resonant metamaterial energy harvester is about 18 times that of the bare plate energy harvester in the outdoor experiments.